The Design and Facility Layout of Traditional Boat-building Based on the Regression Model - Praharsi, Yugowati; Muhammad Abu Jami’in; Agus Khumaidi (Surabaya State Polytechnic of Shipbuilding, 2025)
Traditional fishing boats are used widely by fishermen in Indonesia. However, the design has not been standardized yet. Therefore, it will influence the resistance and the endurance tests. In this study, we aim to design the lines plan model of a fishing boat for the standardization of its components. The regression model is used to determine the length of the keel, the height of the boat, the length of the boat, and the width of the boat. The results show the general arrangement, lines plane design, and facility layout of traditional boats based on the regression model. This study will contribute to the business process development at the shipyard and the small craft technology.